A prospective study of acute corneal hydrops by in vivo confocal microscopy in a New Zealand population with keratoconus. Issue 9 (29th April 2014) - Lockington, David; Fan Gaskin, Jennifer C; McGhee, Charles N J; Patel, Dipika V
Abstract : Background/aims: To analyse the clinical and microstructural changes during the course of acute corneal hydrops in keratoconus. Methods: A prospective study of consecutive patients presenting with acute corneal hydrops over 12 months was performed. Patients were examined with slit-lamp biomicroscopy and in vivo confocal microscopy (IVCM) at 2-weekly intervals until resolution of hydrops. Results: 10 consecutive patients (mean age 23.6±7.5 years) were recruited. All were of Maori or Pacific Island Nations origin. All affected eyes exhibited extensive grade 3 acute corneal hydrops. Mean best corrected vision in hydrops eyes was 2/60 at presentation and 6/48 at resolution. Mean time to resolution of hydrops was 9.9±4.3 weeks. On IVCM, four corneas exhibited hyper-reflective round cells in the epithelium and stroma. Elongated branching cells with small cell bodies were noted in the anterior stroma in two cases at 6 and 12 weeks, respectively. Three months after presentation, both cases also exhibited unusual stromal cells with large speckled cell bodies and elongated branching cell processes. Both cases subsequently developed corneal neovascularisation. Conclusions: Corneal neovascularisation occurred in 20% of eyes in this pilot study and prolonged presence of presumed inflammatory cells was observed in these eyes. Further study of this potential association may enable identification of patients at risk of neovascularisation.